Dramaturgi Hijab Cosplayer Anime Jepang (Jurnal Ilmu Komunikasi dan Bisnis, 2021)
This study discusses about the concept, self-identity and the influences of anime, manga, or games on a Japanese anime hijab cosplayer. This study uses a qualitative method with a phenomenological approach and a dramatic theory of the back and front stage. Based on the research that has been done, the results of this study indicate that hijab cosplayers have a good self-concept and identity are able to differentiate their concept and their identity while doing cosplay. Even though they are use their hijab, hijab cosplayer still can show their own self and do cosplay like other normal cosplayer. Hijab cosplayer will cosplay anime character using hijab. It is because there is support that can help develop their self-confidence. There are no significant changes that can affect the identity of the hijab cosplayers, it's just that sometimes the actions of anime, manga or game characters that have been played have little impact on real life and it doesn't last long.